2018
DOI: 10.1590/0100-29452018764
|View full text |Cite
|
Sign up to set email alerts
|

Performance of ‘Cadenera’ orange trees grafted on five rootstocks

Abstract: Citriculture is an important alternative for the agribusiness development in the state of Paraná, Brazil. However, the use of a few cultivars of scion and rootstock restricts the harvest period and increases the vulnerability to pests and diseases. This study aimed to evaluate the vegetative growth, production and fruit quality of ‘Cadenera’ orange trees (Citrus sinensis (L.) Osbeck ) grafted on five rootstocks, during nine harvests, under a subtropical environmental condition. The experimental design was rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…However, as a rule the quality of the scion fruit is affected by the rootstock, as determined in this study, Amorim et al (2018) did not detect significant differences for the juice yield, acidity, soluble solids, ratio, or technological index characteristics of the 'Cara Cara' Bahia orange and the 'Tahiti CNPMF-02' acid lime grafted onto different rootstocks. Except for the juice yield, Sampaio et al (2016) for the 'Pera' orange and Domingues et al (2018) for the 'Cadenera' orange verified the influence of the rootstocks for these characteristics, also finding higher averages than observed in the present study.…”
Section: /8supporting
confidence: 85%
“…However, as a rule the quality of the scion fruit is affected by the rootstock, as determined in this study, Amorim et al (2018) did not detect significant differences for the juice yield, acidity, soluble solids, ratio, or technological index characteristics of the 'Cara Cara' Bahia orange and the 'Tahiti CNPMF-02' acid lime grafted onto different rootstocks. Except for the juice yield, Sampaio et al (2016) for the 'Pera' orange and Domingues et al (2018) for the 'Cadenera' orange verified the influence of the rootstocks for these characteristics, also finding higher averages than observed in the present study.…”
Section: /8supporting
confidence: 85%
“…However, the growth development characteristics were highly variable among our assessed hybrids, especially when comparing genotypes from the same progenitor rootstocks (for instance, citrumelos and citrandarins). This indicates that these variables may be under the genetic control of several heterozygous loci [40], or that these genotypes carry commercially unattractive characteristics of the parents, as we observed for the trees grown on 'Sunki' and 'Cleopatra' tangerines, which normally have canopies with high vegetative vigor [9,28].…”
Section: Discussionmentioning
confidence: 57%
“…Orange varieties grafted on the 'Rangpur' lime tend to have higher and early production, characteristics that make it one of the most used rootstocks in Brazil [8,9]. The use of early producing scion/rootstock combinations, i.e., those bearing high yields in the first crops, as we observed for 'Valencia' orange trees on 'US-812' citrandarin and 'W-2' citrumelo rootstocks, is a good strategy for ensuring financial return and covering the initial costs when establishing a new orchard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This character is important for higher density orchards than the wide one. Citrus scion grafted on Citrumelo has smaller canopy than grafted on Rangpur lime (Domingues et al 2018). Other researchers reported that citrus scion grafted on Citrumelo and Rangpur lime had the same canopy volume (Gonzatto et al 2011;Bacar et al 2017).…”
Section: Discussionmentioning
confidence: 96%